(untitled) (Research, Society and Development, 2023)
In Piauí, the prevention of maternal mortality started with the actions of the committees: state, regional and inter-hospital, however, the difficulties related to the under-registration of live births and the inadequate completion of the notification forms and declaration of maternal death compromise the indicatives of Piauí reality. The objective, therefore, was to analyze the clinical and epidemiological profile of pregnant women victims of maternal deaths in the state of Piauí. This was an epidemiological, documentary, quantitative research of a descriptive and retrospective nature. It was carried out by collecting public domain data contained in the Mortality Information System (SIM – DATASUS). The study involved the analysis of all maternal deaths reported in the system, in the state of Piauí, from 2009 to 2019. There were 458 deaths, with a higher incidence in 2012, predominantly in young women, between 20 and 29 years old (43%), brown (69%), with 4 to 7 years of schooling (27%), and single (35%). The main place of occurrence were hospitals, in the Mid-North macro-region (34%), during the puerperium (55%), whose main causes were direct obstetrics (69%), with deaths being investigated using the summary form. It can be concluded that maternal death still remains a serious public health problem in the state of Piauí, in a way that it presents itself as a reflection of a precarious reality of health care for the population, associated with socioeconomic inequalities, due to the persistence of maternal deaths from preventable causes, between the years 2009 to 2019, in the younger portion of society in need of assistance and information in the state.